2006
DOI: 10.1091/mbc.e05-04-0360
|View full text |Cite
|
Sign up to set email alerts
|

Nudel Contributes to Microtubule Anchoring at the Mother Centriole and Is Involved in Both Dynein-dependent and -independent Centrosomal Protein Assembly

Abstract: The centrosome is the major microtubule-organizing center in animal cells. Although the cytoplasmic dynein regulator Nudel interacts with centrosomes, its role herein remains unclear. Here, we show that in Cos7 cells Nudel is a mother centriole protein with rapid turnover independent of dynein activity. During centriole duplication, Nudel targets to the new mother centriole later than ninein but earlier than dynactin. Its centrosome localization requires a C-terminal region that is essential for associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 48 publications
8
85
0
Order By: Relevance
“…However, 4.1R epitopes are largely noncoincident with C-Nap1 at the proximal ends of centrioles. We also found that 4.1R epitopes were consistently targeted in tandem with ninein and ODF2 to newly maturing centrioles during centriole duplication, unlike some other proteins, such as Nudel, that arrive after ninein (18). 4.1R localization at centrosomes is not dependent on microtubules (29), and our data reported here suggest that 4.1R may be an integral component of centrioles bearing distal/subdistal appendages.…”
Section: Discussionsupporting
confidence: 66%
“…However, 4.1R epitopes are largely noncoincident with C-Nap1 at the proximal ends of centrioles. We also found that 4.1R epitopes were consistently targeted in tandem with ninein and ODF2 to newly maturing centrioles during centriole duplication, unlike some other proteins, such as Nudel, that arrive after ninein (18). 4.1R localization at centrosomes is not dependent on microtubules (29), and our data reported here suggest that 4.1R may be an integral component of centrioles bearing distal/subdistal appendages.…”
Section: Discussionsupporting
confidence: 66%
“…This family also includes Ndel1 and dynein (Morris et al 1998). Ndel1 is required for targeting Lis1 and dynein to the centrosome, and facilitates the nucleation and anchoring of microtubules to the centrosome (Guo et al 2006). In addition, Ndel1 facilitates the interaction between Lis1 and dynein and regulates dynein-mediated retrograde transport (Gupta et al 2003;Li et al 2005;Mesngon et al 2006;Smith et al 2000).…”
Section: Nucleokinesismentioning
confidence: 99%
“…Dynein at the kinetochore may be involved in kinetochore-microtubule attachment and SAC silencing. 103 The dynein/dynactin complex not only transports a variety of proteins (including several others that promote microtubule nucleation) to the centrosome [104][105][106][107][108] but also nucleates microtubules itself. 109 Dynein/dynactin is also necessary for centrosomal retention and focusing of microtubules, regulation of mitotic spindle positioning and length, and migration of interphase cells.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 99%